Medida da preditividade de instrumentos psicológicos nas avaliações psicológicas de condutores - Silva, Fábio Henrique Vieira de Cristo e (2008)
The object of this study was to identify the possibility of predicting the involvement in traffic infractions from the results of the psychological tests carried out by psychologists specialized in the process of driver licensing in the state of Rio Grande do Norte (RN). The proposal consisted in identifying the penalty points recorded in national driving licenses (CNH) and identifying the corresponding tests and scores obtained, verifying if the average scores in the tests of drivers with and without an infraction record were significantly different and if there is any relation between the test scores and the frequency of the infractions. The results of the psychological instruments were collected in two moments the first being in the act of acquisition of the CNH and the second being during license renewal at the only certified clinic and at the DETRAN-RN. A population of 839 drivers of 14 municipalities were identified. 127 protocols of psychological tests were identified in the records of the DETRAN-RN (2002) and 76 at the clinic (2007), pointing out failures in the process of safekeeping of the psychological material, as well as in its retrieval from the record files. The sample was thus reduced to 68 drivers, all male, with age range between 18 and 41 years old, mean of 21,72 years old (DP = 5,24). 54 drivers were identified without a record of infraction, and 14 with a record. The latter committed 29 infractions. The penalty points recorded in their CNH ranged from 0 to 35 and the typical value of points (median) was zero. In the group with a record of infractions the number of points ranged between 3 and 35, mean of 10,79 (DP = 7,73). Differences were observed in the composition of the battery of tests in the two moments with the same subjects. The use of different tests to assess the same construct of the subject, first and second moment of assessment, did not allow for some analyzes with more efficient statistical proof. It was pointed out that five tests were not carried out and 118 were not corrected/analyzed. Significant differences between the groups were not identified with the psychological instruments used. In another attempt to establish differences between the means, the application of the independent t-Test evidenced a significant difference in the scores of the instruments of concentrated attention in 2002 (t = 2,21, gl = 25, p = 0.037) and of diffuse attention in 2002 (t = 2,37, gl = 24, p = 0.026). The results also did not evidence significant correlation between the scores of the tests and the penalty points of the infractions. Based on this study, it cannot be concluded with precision that the high or low scores are good criteria to determine that a driver will commit more or less traffic infractions, nor that the drivers with higher scores in the tests commit less infractions and vice-versa. Furthermore, the problems to find the instruments and the most basic data require a stronger monitoring on the part of the certified clinic and of the DETRAN-RN.